Stimulators of soluble guanylate cyclase (sGC) inhibit experimental skin fibrosis of different aetiologies. Issue 8 (27th March 2015) - Dees, Clara; Beyer, Christian; Distler, Alfiya; Soare, Alina; Zhang, Yun; Palumbo-Zerr, Katrin; Distler, Oliver; Schett, Georg; Sandner, Peter; Distler, Jörg H W
Abstract : Objectives: Stimulators of the soluble guanylate cyclase (sGC) have recently been shown to inhibit transforming growth factor-β signalling. Here, we aimed to demonstrate that riociguat, the drug candidate for clinical trials in systemic sclerosis (SSc), is effective in experimental fibrosis and to compare its efficacy to that of phosphodiesterase V inhibitors that also increase the intracellular levels of cyclic guanosine monophosphate. Methods: The antifibrotic effects of riociguat and sildenafil were compared in the tight-skin 1 model, in bleomycin-induced fibrosis and in a model of sclerodermatous chronic graft-versus-host-disease (cGvHD). Doses of 0.1–3 mg/kg twice a day for riociguat and of 3–10 mg/kg twice a day for sildenafil were used. Result: Riociguat dose-dependently reduced skin thickening, myofibroblast differentiation and accumulation of collagen with potent antifibrotic effects at 1 and 3 mg/kg. Riociguat also ameliorated fibrosis of the gastrointestinal tract in the cGvHD model. The antifibrotic effects were associated with reduced phosphorylation of extracellular signal-regulated kinases. Sildenafil at doses of 3 and 10 mg/kg exerted mild antifibrotic effects that were significantly less pronounced compared with 1 and 3 mg/kg riociguat. Conclusions: These data demonstrated potent antifibrotic effects of riociguat on experimental skin and organ fibrosis. These findings suggest a role for riociguat for the treatment of fibrotic diseases, especially for the treatment of SSc. A phase II study with riociguat in patients with SSc is currently starting.